Stress, Cortisol, and B-Lymphocytes: A Novel Approach to Understanding Academic Stress and Immune Function - McGregor, Bonnie A (Stress, 2016)
Animal and human in vitro models suggest that stress-related B lymphocyte decrements are due to high levels of glucocorticoids which cause apoptosis of pre-B-cells as they emerge from the bone marrow. The present study sought to explore the relationships among distress, salivary cortisol and human B lymphocytes in vivo. Distress (perceived stress, negative affect, depressive symptoms), lymphocyte phenotype, and salivary cortisol were assessed among first year graduate students (n=22) and a community control sample (n= 30) at the start of classes in the fall and the week immediately before spring preliminary exams. Compared to controls, students reported greater distress on all measures at each time point except baseline perceived stress. Hierarchical linear regression with necessary control variables was used to assess the effect of student status on the three measures of distress, the four measures of lymphocyte phenotype, and cortisol AUC and CAR over time (T1-T2). Student status was associated with a significant decrease in CD19+ B lymphocytes and flattened cortisol awakening response (CAR). Change in CAR was associated with the decrease in CD19+ B lymphocytes. Results indicated that there are significant associations among student status, flattening of CAR, and decrements in CD19+ lymphocytes.